PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA CV. NETRAL KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Dewi, Kurnia (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research is on CV. Netral Rengat District, Indragiri Hulu Regency. The purpose of this research is to know the effect of service quality and price simultaneously on customer satisfaction on CV. Neutral Rengat District, Indragiri Hulu Regency; To find out the effect of service quality partially on customer satisfaction on CV. Neutral Rengat District, Indragiri Hulu Regency; To find out the effect of prices partially on customer satisfaction on CV. Neutral Rengat District, Indragiri Hulu Regency. The population in this study are all consumers who use the services of CV. Neutral Rengat Subdistrict, Indragiri Hulu Regency which is infinite in number, where visitors are teenagers to adults, the population used is 24,057 people. While the sample in this study amounted to 100 people with a nonprobability sampling technique. Thisr research used quantitative methods, namely by multiple linear regression, correlation coefficient and determination, and F test and t test. Based on the results of the research and discussion, some conclusions can be drawn as follows: From the quantitative calculations obtained using the multiple linear regression equation Y = a + b1X1 + b2X2 obtained Y = 3.808 + 0.238 X1 + 0.528 X2, namely the constant coefficient value (a) amounting to 3.808 this means that if the value of service quality (X1) and price (X2) equals zero, then the level or amount of customer satisfaction (Y) is equal to 3.808. The coefficient value of X1 = 0.238 means that if the service quality (X1) rises by one unit, while the price variable (X2) remains, customer satisfaction (Y) will increase by 0.238 and vice versa if the service quality (X1) decreases by one unit, while the price variable (X2) remains, consumer satisfaction (Y) will decrease by 0,238. The coefficient value of X2 = 0.528 explains that if the price (X2) rises by one unit, while the service quality variable (X1) remains, the level of customer satisfaction (Y) will increase by 0.528 and if the price (X2) falls by one unit, while the service quality variable (X1) remains that consumer satisfaction (Y) will decrease by 0.528. Multiple linear correlation coefficient (R) that is 0.885 means that the relationship that has a very high correlation between service quality and price to customer satisfaction is 0.885. The coefficient of determination (R2) is 0.783, meaning that customer satisfaction can be explained by variations in changes in the independent variable (service quality and price) of 78.3%, while the remaining 21.7% is explained by other variables outside the research. Based on the results of the F test, the calculated F value is 175,051 with a significant level of 0,000. While Ftable at 100% (0.05) is 3.09. In both calculations, F count> Ftable is 175,051> 3,09. This means that Ho is rejected and Ha is accepted, meaning that simultaneously service quality and price have a significant effect on customer satisfaction. Based on the results of the t test obtained the value of tcount X1> t table = 2.101> 1.98447 so that Ho is rejected and Ha is accepted, which means the independent variable (X1) service quality partially has a significant effect on the variable customer satisfaction (Y). Furthermore, the value of tcount X2> t table = 4.268> 1.98447 so that Ho is rejected and Ha is accepted, which means that the independent variable (X2) price partially has a significant effect on the variable customer satisfaction (Y).